Pengenalan Pemakaian Tanjak Melayu Pada Mahasiswa Sastra Daerah Fakultas Ilmu Budaya - Ulul Azmi; Essy Syam; Qori Islami Aris (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2020)
This service aims to introduce the use of Malay tanjak to students and provide understanding and awareness about the need to know the use of Malay tanjak in daily life. Tanjak is a tradition and identity of the Malay community. Tanjak is one of the clothing accessories for men in Malay, the tanjak is used on the head as a symbol of Malay society. Tanjak has a symbol of authority among the Malay community, the higher and more complex the shape will show the higher social status of the owner. Tanjak is usually used by men when they want to go out, like a skull cap. Tanjak is commonly used by Malay people in all layers of social class, both in the form of royal support as aristocrats and lower classes of society. The development of life which is followed by the development of technology and the inclusion of foreign culture slowly shifts the existence of the use of Malay inclines. Previously, not using a hill was considered to violate adat. Therefore, the use of tanjak is a true Malay identity. The use of the Malay hill was reintroduced because many people did not know it, one of which was the use of the hill climb for sultans, commanders and ordinary people, the way to use the Malay hill was certainly very different from one another, for which students could later apply the use of the Malay hill to the community.